2018
DOI: 10.3390/cancers10110454
|View full text |Cite
|
Sign up to set email alerts
|

Severe Neutropenia is Associated with Better Clinical Outcomes in Patients with Advanced Pancreatic Cancer Who Receive Modified FOLFIRINOX Therapy

Abstract: While modified FOLFIRINOX therapy is effective for treating advanced pancreatic cancer, it frequently causes severe neutropenia. The present study investigated the effect of severe neutropenia on clinical outcomes in advanced pancreatic cancer patients who received modified FOLFIRINOX. The study subjects were 51 patients (30 males and 21 females) with advanced pancreatic cancer who received modified FOLFIRINOX (2h bolus injection of oxaliplatin at 85 mg/m2, 2 h bolus injection of L-leucovorin at 200 mg/m2, 90m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
10
1
Order By: Relevance
“…In 2011, the PRODIGE4/ ACCORD11 trial showed that FOLFIRINOX led to longer survival rates when compared to gemcitabine monotherapy 24 . In 2018, a study investigated the effect of severe neutropenia on clinical outcomes in advanced pancreatic cancer patients who received modified FOLFIRINOX 25 . This study assessed a total of 51 patients treated from January 2014 until May 2018.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, the PRODIGE4/ ACCORD11 trial showed that FOLFIRINOX led to longer survival rates when compared to gemcitabine monotherapy 24 . In 2018, a study investigated the effect of severe neutropenia on clinical outcomes in advanced pancreatic cancer patients who received modified FOLFIRINOX 25 . This study assessed a total of 51 patients treated from January 2014 until May 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Considering patients that received modified FOLFIRINOX, Yamada et al [98], found that the development of neutropenia after chemotherapy correlates with better OS. Moreover, there was a significant correlation between OS and the grade of neutropenia.…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…Neutropenia, as well as NLR decrease, indicate systemic inflammation receding. 38 , 39 The timing of neutropenia is an independent predictor of prognosis in metastatic colon cancer patients who received mFOLFOX6. Moreover, patients with early-onset and late-onset chemotherapy-induced neutropenia (CIN) had longer survival than patients without CIN.…”
Section: Discussionmentioning
confidence: 99%